Efek Protektif Penggunaan Antiradiasi Alpha Spin Terhadap Histologi Hipokampus Tikus Putih (Rattus novergicus) Galur Sprague dawley yang Terpapar Gelombang Elektromagnetik Ponsel - Ahmad Rizki Dwi Prasetia; Waluyo Rudiyanto; Merry Indah Sari (Journal of Health Science and Physiotherapy, 2020)
Exposure to cellphone electromagnetic radiation can cause oxidative stress which can later lead to changes in the hippocampal pyramidal cells. This change can be characterized by a reduction in the number of pyramidal cells and a change in cell morphology characterized by occurrence of picnosis or hydropic degeneration in the hippocampal pyramidal cell nucleus. Alpha Spin can inhibit cell phone electromagnetic radiation exposure through the quantum energy field formed by Alpha Spin. This study aims to determine the protective effect of the use of Alpha spin antiradiation on the histology of the hippocampus of white rats (Rattus norvegicus) Sprague dawley strains exposed to mobile electromagnetic waves. Laboratory experimental research using randomized controlled methods with a post test only control group design. Samples were 30 white rats divided into 3 groups. The control group (K) was only given food and drink, the treatment group 1 (P1) was exposed to cellphone electromagnetic waves and the treatment group 2 (P2) was exposed to cellphone electromagnetic waves and placed Alpha Spin. Exposure is done 2 hours / day for 30 days. There were mean differences in all groups with a significant value, which was p <0.05. There is a protective effect of Alpha Spin antiradiation on the histology of the hippocampus white rat (Rattus norvegicus) Sprague dawley strain that is exposed to cellphone electromagnetic waves.